Myoepithelioma of the soft tissue: A systematic review of clinical reports. Issue 9 (September 2019) - Rastrelli, Marco; Del Fiore, Paolo; Damiani, Giovanni Battista; Mocellin, Simone; Tropea, Saveria; Spina, Romina; Costa, Alessandra; Cavallin, Francesco; Rossi, Carlo Riccardo
Abstract: Background: Myoepithelioma of the soft tissue (MES) is a rare neoplasm, and available literature includes few studies with small sample sizes, thus limiting the comprehension of this disease. Hence, a systematic review was performed to summarize the available information on MES patients evaluated for surgical treatment. Methods: The MEDLINE/PubMed, EMBASE and SCOPUS databases were reviewed for eligible studies in January 2019. Inclusion criteria were: patients with MES; indication for wide resection or amputation; observational studies; articles published from 1997 to 2018; English language; reporting of outcome measures such as overall survival (OS), disease-free survival (DFS), recurrence, metastases. Studies not including humans were excluded. Quality appraisal was performed using the Methodological Index for Non-Randomized Studies (MINORS) tool. A narrative synthesis of included studies was conducted, a formal meta-analysis being unfeasible. Results: Overall, 10 eligible studies including 233 MES patients were identified. The most frequent tumor sites were the limbs and trunk. Most patients underwent surgical treatment, with R0 resection margin rates ranging from 24% to 78%. During follow-up, local recurrence rates ranged from 17% to 50, and distant metastasis rates varied 8%–48%. At 5 years, OS rates ranged from 8% to 94% and DFS rates from 11% to 40%. The average MINORS score was 9.1 (range: 6–11). Conclusions: Surgical resection was often sub-optimal. The long-term prognosis was poor, with a non-negligible rate of disease recurrence and metastasis. On average, the quality of available information is moderate. The centralization of patient information in large international registries is warranted to provide a better understanding of MES biology and ultimately improve patient outcomes.